Conjugational verb types as prototype based categories - Jelaska, Zrinka (Array, 2012)
Slavic grammarians, Croatian in particular, categorize verbs into conjugational types from different points of view. This paper tries to find foundations of conjugational verb type categorization in the cognitive linguistics framework (e.g. Langacker 1987, 1991, Taylor 2003). It views conjugational verb typology as prototypically organized category (e.g. Rosch 1978, Tabakowska 2005), which has to be relevant to a language community as category is the conceptualization of "a collection of similar experiences that are meaningful and relevant to a language community" (Radden, Dirven 2007). In line with cognitive linguistics, the authors believe that grammatical categories have structural meanings, even phonological (e.g. Taylor 2003, Jelaska, Gulešić-Machata 2005) and analyze phonological differences in conjugation defining forms in relation to morphological and (verbal) meaning differences which could be assigned to the types as categories. The data consists of more than 24 000 Croatian verbs which are categorized into groups, types and subtypes that display different degrees of membership. Conjugational verb types are defined by their phonological and morphological shape, which predict their phonological changes in flection. The relationship between infinitive, the most non-finitive verbal form, and present, which is on the other side of the finiteness scale, is enough to categorize a verb into a conjugational type. Verb types are members of a category verb groups (a, i, e), while verb subtypes may be included in a type (e.g. prijateljevati vs. umirivati within putovati type). Many less prototypical types are made of complex, derived members. The findings on the role of frequency are confirmed by two experiments where students were asked to list ten or twenty verbs, with the hypothesis that the most salient verb types (e.g. verbs of prototypical types) will be frequently listed and high on the list. Type of Croatian verbs such as gledati are considered a prototype of the conjugational category. It is phonologically transparent, the largest conjugational category, spreadable (yet the percentage of prefixed verbs is very low), completely open, very productive, frequent (based on individual verbs which appear in the basic Croatian vocabulary), predictable, recognizable from present forms ; it is the only member of a group. Other types differ from the prototypical one as they do not share one or more of those properties, or have it to a lesser degree. The closest to the prototype is type moliti, but its size depends on spreadity more than in the prototype, it is less phonologically transparent in some forms, somewhat less open. Types such as voljeti, plesati, trčati, are considered to be less prototypical members, while poznavati is seen as a peripheral member of the category type. The most salient properties for the judgment besides phonological forms seem to be morphological simplicity (non-derived verbs) and frequency (the percentage of its members in the basic vocabulary, particularly within the most common hundred words). Within small size types the ones with more lexical meaning are viewed as more prototypical.